Correlation between Facial Skin Damage Due to UV Exposure and Facial Skin Porphyrin Level: Study on Students of SMA Kalam Kudus II Jakarta, Indonesia - Fendy Wellen; Sukmawati Tansil Tan; Yohanes Firmansyah; Hendsun Hendsun (HM Publisher, 2023)
Background: UV exposure causes physical and chemical damage. UV causes damage to the skin barrier physically due to the heating process. Meanwhile, chemically, UV causes the formation of oxidants which are responsible for the process of oxidative stress. Damage to skin cells causes loss of the body's natural barrier against various threats from microorganisms. Propionibacterium acnes is one of the commensal bacteria on the skin, which will produce products in the form of porphyrins. This study aimed to determine the correlation between UV-induced skin damage and porphyrin levels in SMA Kalam Kudus II Jakarta, Indonesia. Methods: This study was an analytic observational study with a cross-sectional approach. A total of 92 research subjects who were students of SMA Kalam Kudus II Jakarta, Indonesia, participated in this study. Facial skin porphyrin levels and levels of facial skin damage due to sun exposure (UV damage proportion) as measured by a skin analyzer. UV damage and porphyrin assessments according to the T Zone and V Zone regions and obtained the average results from the 3 regions. Correlation analysis was performed with the help of SPSS software. Results: The higher the percentage of skin damage due to UV correlated positively with the higher the percentage of porphyrin levels, with a value of r = 0.529. Conclusion: There is a positive correlation between UV-induced skin damage and porphyrin levels in students of SMA Kalam Kudus II Jakarta, Indonesia.